TITLE: LOVE IN EAST AND WEST: A COMPARISON OF "ROMEO AND JULIET" AND "LAYLA AND MAJNUN" - Xusanova Mukaddas Mavlonovna , (TADQIQOTLAR.UZ, 2024)
Abstract: This article devoted to compare Love in East and West: A Comparison of "Romeo and Juliet" and "Layla and Majnun" It discusses the differences and similarities of these two novels.